EXPLORING ISLAMIC LEADERSHIP ON SME PERFORMANCE: MEDIATED BY INNOVATIVE WORK BEHAVIOR AND FINANCIAL TECHNOLOGY - Febriani, Rizki; Sa'diyah, Chalimatuz (Jurnal Aplikasi Manajemen, 2021)
The current condition of the Indonesian economy is far different from that of the economy ten years ago. One of the differences in the structure and construction of the Indonesian economy compared to 10 years ago is the rapid development of the digital economy and the 4.0 industrial revolution. This study examines the relationship between Islamic Leadership and SME Performance with the Mediation of Innovation Work Behavior and Financial Technology in the Indonesian Muslim Entrepreneurs Community. This type of research uses an explanatory research method. All members of the Indonesian Muslim Entrepreneurs Community, with a sample of 100 entrepreneurs, were among the population in this report. The research method used is the Smart-PLS method. The findings of this study demonstrate that through the mediation of innovative work behavior, Islamic leadership impacts SME performance. So it is hoped that Muslim entrepreneurs can improve this innovative behavior with broader insights and an open attitude to change. It is expected that further research will expand the discussion by adding other variables that have not been studied in this study and also bring up research novelty.